Synthesis of 6,6’-Diaminomethyl-tris-(pyridin-2-ylmethyl)amine - Duan, Zhen-Juan; Zhang, Zi-Qi; Gao, Xue-Jiao; Ma, Chun-Yue; Wang*, Shuo (Asian Journal of Chemistry, 2013)
A new tripodal receptor 6,6'-diaminomethyl-tris-(pyridin-2-ylmethyl)amine was designed, synthesized and characterized by 1H NMR, 13C NMR and IR analysis.